Congenital hepatic fibrosis with congenital heart disease. A family study with ultrastructural features of the liver. Issue 9 (September 1980) - Naveh, Y; Roguin, N; Ludatscher, R; Auslaender, L; Schramek, A; Aharon, M
Abstract : A family with congenital hepatic fibrosis (CHF) and congenital heart disease (CHD) is presented. The consanguineous healthy parents gave birth to 12 children of whom 10 survived. One son had CHF and CHD, one daughter had CHF and a second daughter had CHD. Three other siblings probably had small a ventricular septal defect and another one probably had mild pulmonary valve stenosis. Development of portal hypertension and hypersplenism necessitated performing shunt operation on both siblings suffering from congenital hepatic fibrosis. Ultrastructural findings were giant mitochondria with large laminar inclusions in hepatocytes, and excess of villi and whorls of membranes and collagen fibrils between hepatocytes.